Re-hackling flax before spinning: Using questions as a method of understanding - Ekstedt Bjersing, Marie (FormAkademisk, 2023)
Flax is a traditional plant used to make textiles. Flax, like all natural fibres, is a material with variations. Knowledge of a crafting process can be obtained by studying artefacts and all available documentation and by being present in a craft tradition and society of spinning. A craftsperson will make many small decisions during their work. How do we gain knowledge about handling materials, and how do we preserve the intangible skills relevant to a craft? This performance article aims to make visible specific knowledge of material, tools and working methods for re-hackling flax. The text and performance illustrate the perspective of a reflecting craftsperson. By asking questions about the work process, critical decisions regarding crafts will be highlighted. This approach will help preserve and transmit craft skills within flax processing.